LITERACY AND ALPHABETIZATION AS EMANCIPATORY PRAXIS: KNOWLEDGE MEDIATION, SOCIAL JUSTICE, AND INCLUSION IN THE CONTEMPORARY SCHOOL CONTEXT - Rodrigues, Renato (Seven Editora, 2025)
This article discusses literacy from a critical, dialogical and emancipatory perspective, based on authors such as Ferreiro, Teberosky, Freire, Gadotti, Freinet, Smolka, Soares, Vygotsky, Wallon, Piaget, Makarenko, Guareseci, Masetto and Pestalozzi. Reading and writing are understood as historical, social and cultural processes that go beyond decoding, emphasizing teacher mediation, social justice, democracy and educational inclusion. Learning is analyzed as a social practice guided by praxis, affectivity, love, and non-authoritarian classroom organization. It is argued that schools must recognize students’ realities and experiences, promoting activities that connect theory and practice and encourage critical participation. Literacy, therefore, becomes a political and ethical act aimed at forming critical subjects capable of transforming their social contexts. DOI: https://doi.org/10.56238/sevened2025.038-073